ISOLASI BAKTERI PENDEGRADASI MINYAK /LEMAK DARI BEBERAPA SEDIMEN PERAIRAN TERCEMAR DAN BAK PENAMPUNGAN LIMBAH - Budiarsa Suyasa, I W. (Bumi Lestari; Vol 7 No 1)
Active mud represent process processing of biology by aerobic by using system of suspended growth. Microorganism staying in form of suspended referred also solid suspended liquor mixed ( SSLM), work by fastening organic substrate later then elaborating it with enzyme of exocelluler so that become its dissolve. Process resolving of compounds of organic, microorganism get the source of and carbon of energy. Mud suspended conducted by 1 g follow the example of Mud or sediment thinned with physiological condensation ( 8,5 NaCl g / L) and dissolve up to 10-4 ,or can be conducted by taking 0,5 g of sediment into tube reaction of containing 4,5 physiological salt condensation then shake to get homogeneous suspended. suspended and disseminated by containing solder cup on specific media, and then incubation at temperature 270C during 24 - 48 hour. Obtained by isolate of RPH1,RPH2, PP, SBDG and STT. During process of seeding measured parameters, there are VSS and COD that measured base on time during treatment. Its process was result RPH2 isolate that showing higher growth of microbiologist activity then another. Result of the research showing that VSS and COD has highest during treatment.
Keywords: sediment, mud suspended, seeding